STUDENTS’ DIFFICULTIES IN WRITING NARRATIVE TEXT - Manisha Koilara; Four Satria Tambunan; Diana Romaito Hutabarat; Sri Ninta Tarigan (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research aims to describe students' difficulties in writing narrative texts, the students' more dominant problems and to know English teacher action to solve the problem. The researchers used qualitative research and a descriptive case study. This study tries to observe students' mistakes in writing narrative texts. The data collected based on the students' answer sheet. The categories made based on the students' answer sheets in writing Narrative texts. The things that recorded by the researchers for giving scores are the four generic structures: Orientation, Complication, Resolution, and Re-Orientation/Coda. And the researchers found that the students still had difficulties in writing narrative texts with the generic structures. Based on the findings, from 26 students only 3 students can distinguish between parts of generic structures and the rest must practice at home and ask the teacher to make improvements.